2012
DOI: 10.3892/ijmm.2012.911
|View full text |Cite
|
Sign up to set email alerts
|

Tgf-β1 induces autophagy and promotes apoptosis in renal tubular epithelial cells

Abstract: Abstract. Transforming growth factor-β1 (TGF-β1) is a multifunctional cytokine that regulates cell growth, differentiation, apoptosis and autophagy in various cell types. It has been shown that TGF-β1-driven autophagy represents a novel mechanism of tubular decomposition, leading to renal interstitial fibrosis. However, the exact mechanism by which TGF-β1 regulates autophagy is still poorly understood. In the present study, we investigated the effects of exogenous TGF-β1 on cultured human renal proximal tubula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 23 publications
1
68
0
Order By: Relevance
“…35 Later studies further demonstrate autophagy induction by TGFB1 in primary mouse proximal tubular cells and cultured human renal proximal tubular cells. 32,47 Consistently in the current study, autophagy activation by TGFB1 was also shown in both primary culture and cell line of proximal tubular cells (Figs. 8, 10).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…35 Later studies further demonstrate autophagy induction by TGFB1 in primary mouse proximal tubular cells and cultured human renal proximal tubular cells. 32,47 Consistently in the current study, autophagy activation by TGFB1 was also shown in both primary culture and cell line of proximal tubular cells (Figs. 8, 10).…”
Section: Discussionsupporting
confidence: 91%
“…34 In addition, TGFB1 induces the upregulation of several autophagy-related genes, such as ATG5, ATG7, and BECN1, in cultured human renal proximal tubular cells. 47 Under this condition, induction of autophagy is associated with an increased generation of reactive oxygen species and enhanced expression of NADPH (reduced NAD phosphate) oxidases. 47 In addition to TGFB1, regulation of autophagy by HIF1A (hypoxia inducible factor 1, a subunit) to activate hepatic stellate cells during liver fibrosis has been suggested recently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-␤1 stimulation induced the accumulation of autophagosomes and conversion of LC3 to the lipidated form, LC3-II, and upregulated autophagy-related genes ATG5, ATG7, LC3, and Beclin 1 in renal tubular epithelial cells (19,42,97). We also recently reported that TGF-␤1 induced autophagy in glomerular mesangial cells (18,40).…”
Section: Tgf-␤ Signaling and Autophagymentioning
confidence: 71%
“…Production in Human Renal Tubular Endothelial Cells Renal tubular epithelial cells (rTECs) express Noxs, 40,41 including Nox1 and 2, 42,43 and are a target of cell injury driven by O 2 z2 . 3 To determine whether TSP1-SIRP-a-mediated stimulation of O 2 z2 is a general finding and extends to other parenchymal cells, we treated human rTECs with TSP1.…”
Section: ·2mentioning
confidence: 99%